Environmental Rights and Rights of Nature: A Comparative Analysis between the Constitutions of Brazil (1988) and Ecuador (2008) - Viana da Silva, Marcos Vinicius; de Freitas Pereira, Lorena Victória; da Rosa, Victória de Oliveira (Ius Humani. Jornal do direito, 2025)
This study conducts a comparative analysis of environmental rights and the rights of nature as established in the Constitutions of Brazil (1988) and Ecuador (2008). The research, based on a qualitative approach, highlights how each country has incorporated ecological principles into its legal frameworks, reflecting distinct historical, cultural, and political contexts. In Brazil, the 1988 Constitution enshrines the right to an ecologically balanced environment, emphasizing the protection of natural resources and the promotion of sustainable development. This approach, centered on environmental protection for human benefit, has been implemented through a robust legal framework that, however, faces challenges related to institutional fragmentation, conflicts of interest, and difficulties in enforcement across a country of continental dimensions. In contrast, Ecuador adopted an innovative perspective by recognizing nature as a subject of rights, granting it legal personhood and emphasizing an ecocentric vision that integrates Indigenous knowledge and traditional practices. While conceptually advanced, this innovation also encounters practical obstacles in reconciling economic development with ecosystem protection. Comparative analysis reveals convergences in the pursuit of sustainability and environmental protection, as well as divergences in implementation and governance strategies. This study highlights the importance of integrated policies and intersectoral collaboration to overcome environmental challenges, thereby promoting an effective balance between economic development and ecological preservation.